Feasibility of assessing bone matrix and mineral properties in vivo by combined solid-state (1)H and (31)P MRI - Zhao, Xia (PLoS One, 2017)
PURPOSE: To develop and evaluate an integrated imaging protocol for bone water and phosphorus quantification in vivo by solid-state (1)H and (31)P MRI. MATERIALS AND METHODS: All studies were HIPAA-compliant and were performed with institutional review board approval and written informed consent. Proton ((1)H) ultra-short echo-time (UTE) and phosphorus ((31)P) zero echo-time (ZTE) sequences were designed and implemented on a 3 T clinical MR scanner to quantify bone water and mineral in vivo. The left tibia of ten healthy subjects (including both genders, 49±15 y/o) was examined with a custom-built (1)H/(31)P dual-frequency extremity RF coil. Total bone water (TW), water bound to the collagen matrix (BW) and bone (31)P were quantified from MR images with respect to reference samples of known (1)H or (31)P concentration, and pore water (PW) was subsequently determined from TW and BW. Porosity index (PI) was calculated as the ratio between UTE images acquired at two echo times. MRI parameters were compared with bone density measures obtained by high-resolution peripheral quantitative CT (HR-pQCT). RESULTS: The total scan time for the bone water and (31)P quantification protocol was about 50 minutes. Average TW, BW, PW and (31)P concentrations were 13.99±1.26, 10.39±0.80, 3.34±1.41 mol/L and 7.06±1.53 mol/L for the studied cohort, respectively, in good agreement with previous results conducted ex vivo. Average intra-subject coefficients of variation were 3.47%, 2.60% and 7.50% for TW, BW and PW and 5.60% for (31)P. Negative correlations were observed between PW and vBMD (p<0.05) as well as between PI and (31)P (p<0.05), while bone mineral content (BMC) estimated from (31)P MRI and HR-pQCT were strongly positively correlated (p<0.0001). CONCLUSION: This work demonstrates the feasibility of quantifying bone water and mineral phosphorus in human subjects in a single MRI session with a clinically practical imaging protocol.